Pelatihan Pengenalan Komputer untuk Meningkatkan Kualitas SDM di SDN 1 Demung Besuki - Muafi; Achmad Rohman; Abdul Khoir; Hasyim , Fuadz; Abdul Malik Muhammad Khibar (Insan Kreasi Media, 2023)
Abstract: SDN 1 Demung Besuki is a public school located in the western part of Situbondo Regency. The school has ±10 teachers and has ±102 students. Knowledge of computer technology for HR at SDN 1 Demung Besuki, especially students, is currently still very low. This is known from the knowledge of some students who are still not proficient in operating computers. In addition, students rarely use or even never use computers because many students do not have computers and the lack of existing computer laboratory facilities. Currently, the use of computers is only used by schools and teachers. Therefore, basic computer introduction training is needed for SDN 1 Demung Besuki students to improve the quality of existing students. The method used is through observation and preparation, implementation and evaluation. The result of this proportion training is that students can manage computer equipment properly and correctly, namely 80% of the total who attended the training and students who can manage word processing applications / Ms Word properly and truly are 85% and 78% of students who can manage number processing applications / Ms Excel properly and correctly..